2014
DOI: 10.1002/hlca.201300382
|View full text |Cite
|
Sign up to set email alerts
|

Three New Pentacyclic Triterpenoids from Centella asiatica

Abstract: Three new pentacyclic triterpenoids, named centellasaponin I (1), centellasaponin J (2), and centellasaponin E (3), together with three known compounds, were isolated from the whole plants of Centella asiatica. Their structures were elucidated on the basis of chemical and spectral analysis, including 1D‐ and 2D‐NMR and HR‐MS experiments, and by comparison with literature data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The absolute configurations of the sugar residues were determined to be D-glucose and L-rhamnose by the method previously reported. 16 The 1 H and 13 C NMR spectra of compound 1 resembled those of asiaticoside B (8), except for the presence of two double bonds in compound 1. The absorption band at 284 nm in the UV spectrum indicated that these two double bonds were conjugated, 19 which were further confirmed to be located at Δ 9,11 1 and 2) of compound 2 resembled those of compound 1 for rings A−D and the sugar residues.…”
Section: ■ Results and Disscusionmentioning
confidence: 91%
See 3 more Smart Citations
“…The absolute configurations of the sugar residues were determined to be D-glucose and L-rhamnose by the method previously reported. 16 The 1 H and 13 C NMR spectra of compound 1 resembled those of asiaticoside B (8), except for the presence of two double bonds in compound 1. The absorption band at 284 nm in the UV spectrum indicated that these two double bonds were conjugated, 19 which were further confirmed to be located at Δ 9,11 1 and 2) of compound 2 resembled those of compound 1 for rings A−D and the sugar residues.…”
Section: ■ Results and Disscusionmentioning
confidence: 91%
“…Compound 4, a white powder, showed a HRESIMS peak at m/z 989.4960 [M + H] + , suggesting a molecular formula of C 48 H 76 O 21 . By comparison of the 13 C and 1 H NMR data (Tables 1 and 2) of compound 4 to those of compound 3, it was easy to conclude that the differences between these two compounds were the same as those between compounds 1 and 2, indicating that compound 4 bore a ursane-type aglycone. Extensive analysis of the DEPT, 1 H− 1 H COSY, HSQC, NOESY, and HMBC spectra further confirmed the structure of compound 4 as 2α,3β,6β,23-tetrahydroxy-11-oxo-urs-12-ene-28-oic acid 28-O-α-L-rhamnopyranosyl(1→4)-β-Dglucopyranosyl(1→6)-β-D-glucopyranoside, named 11-oxo-madecassoside.…”
Section: ■ Results and Disscusionmentioning
confidence: 96%
See 2 more Smart Citations
“…Słowa kluczowe: tymianek, rozmaryn, szałwia, majeranek, oregano, bazylia, fenolowe przeciwutleniacze [Zainol et al 2003]. Given its content of various biologically active substances, the species has been used in the pharmaceutical [Mala andTulika 2015, Roy andBharadvaja 2017], cosmetic [Singh-Verma 2002], and food industries as a food additive [Hashim et al 2011]. The aim of the study was to present bioactive substances identified in Centella asiatica (L.) Urb.…”
Section: Związki Biologicznie Czynne W Ziołach Stosowane Do Mięsa I Pmentioning
confidence: 99%